CURRICULUM DEVELOPMENT CONSIDERING FORMAL, NON-FORMAL AND INFORMAL EDUCATION - Läänemets, Urve; Kalamees-Ruubel, Katrin; Kiilu, Kristi; Sepp, Anu (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Curriculum development for general comprehensive and also vocational schools needs consideration of the context, in which availability of non-formal and informal education (extracurricular activities=EA) plays an important role forming a meaningful whole with formal education. This pilot study attempted to find out what motivates students (aged 13–15) for participation and teachers organizing/supervising these activities. The methods used for data collection were questionnaires for students (n=258), focus groups of students (n=4), and interviews with teachers (n=8) which provided preliminary data for comprehension of the meaning of EA. The data were processed statistically and by content analysis. The results highlighted several important issues which should be considered when selecting and organizing the content for designing subject syllabi for formal learning specified in national curricula (NC) under changed learning environments, especially considering those created by ICT. Students mentioned the following factors: development of students’ self-awareness about ones abilities, acquisition of new knowledge a and skills, but also new friends and wider social contacts, new experience and satisfaction with creative work. The teachers mentioned students’ additional knowledge and skills they can use in their formal studies at school and engagement in activities widening their cultural horizons. EA can also provide material for decision-making for students’ potential choices for future education.